2014
DOI: 10.1128/jvi.00672-14
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Activity of the Pestiviral RNase E rns as an Interferon Antagonist after Uptake by Clathrin-Mediated Endocytosis

Abstract: The RNase activity of the envelope glycoprotein E rns of the pestivirus bovine viral diarrhea virus (BVDV) is required to block type I interferon (IFN) synthesis induced by single-stranded RNA (ssRNA) and double-stranded RNA (dsRNA) in bovine cells. Due to the presence of an unusual membrane anchor at its C terminus, a significant portion of E rns is also secreted. In addition, a binding site for cell surface glycosaminoglycans is located within the C-terminal region of E rns . Here, we show that the activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 55 publications
(70 reference statements)
1
59
2
Order By: Relevance
“…In this study, we investigated for the first time the cell entry process of CSFV particles through dynamin-dependent, clathrin-mediated endocytosis with a pH-dependent step, consistent with the clathrin-mediated endocytosis used by BVDV, another pestivirus (20,59). Additionally, we determined that Rab5 and Rab7 are involved in CSFV entry into PK-15 cells.…”
Section: Discussionmentioning
confidence: 76%
“…In this study, we investigated for the first time the cell entry process of CSFV particles through dynamin-dependent, clathrin-mediated endocytosis with a pH-dependent step, consistent with the clathrin-mediated endocytosis used by BVDV, another pestivirus (20,59). Additionally, we determined that Rab5 and Rab7 are involved in CSFV entry into PK-15 cells.…”
Section: Discussionmentioning
confidence: 76%
“…Recently, two publications reported on the crystal structure of N pro (Gottipati et al, 2013;Z€ ogg et al, 2013). Both groups used aminoterminally truncated N pro expressed in bacteria for crystallization.…”
Section: N Promentioning
confidence: 99%
“…Both groups used aminoterminally truncated N pro expressed in bacteria for crystallization. The starting sequences were derived from a HoBi-like BVDV-3 strain or CSFV strain Alfort 187, and the N-terminal truncations encompassed residues 2-21 or 1-17 (Gottipati et al, 2013;Z€ ogg et al, 2013). Such N-terminal deletions do not interfere with N pro functions (Hilton et al, 2006;Ruggli et al, 2009;R€ umenapf et al, 1998).…”
Section: N Promentioning
confidence: 99%
“…Full-length and ⌬17N N pro have been shown to be functionally identical with respect to their protease and interferon antagonistic activities (20,30,34). Native gel shift assays showed that in the presence of either full-length or ⌬17N N pro , the IRF3 protein band shifted to a higher molecular mass (Fig.…”
Section: Csfv Nmentioning
confidence: 93%
“…The secreted form of E rns is released into the extracellular space, where a role of E rns for degradation of extracellular viral dsRNA and single-stranded RNA molecules has been postulated (17)(18)(19). Interestingly, E rns can enter cells by clathrin-dependent endocytosis and digest viral RNA in endolysosomal compartments via its RNase activity before they can trigger type I IFN induction (20). Importantly, E rns is very efficient at preventing activation of plasmacytoid dendritic cells (pDCs) in contact with CSFV-infected cells (21).…”
mentioning
confidence: 99%